Pemberdayaan Masyarakat Melalui Literasi Keuangan Dalam Masa Pandemi Covid 19 Di Desa Yosowilangun Gresik - Wasti Reviandani; Suaibatul Aslamiyah (Program Studi Manajemen Universitas Muhammadiyah Gresik, 2021)
Community service is carried out in Yoowilangun village, Manyar Gresik sub-district. The COVID-19 pandemic has an impact on increasing the number of open unemployment in the community, and has an impact on decreasing income levels (economic crisis). Community empowerment efforts are carried out starting with understanding the community and its dynamics. The understanding needed is an understanding of the social order and community institutions as well as education related to financial management through financial literacy. The purpose of community service is to identify forms of community empowerment programs based on the potential and problems of Village Development during the COVID-19 pandemic, increase knowledge, skills of the main village communities related to financial management through financial literacy, understanding of bank financial institutions and fostering the entrepreneurial spirit of rural communities through business strategies during the pandemic. . The service method is carried out online by providing education about applications that can be used in managing finances and competitive strategies to survive during the covid 19 pandemic. The results of the service are in the form of understanding the stages of financial literacy, the use and benefits of cash book applications, understanding the main banking about granting credit and marketing strategies during the pandemic.